International child law - Buck, Trevor (Routledge, 2014)
" International Child Law examines and discusses the international legal framework and issues relating to children. Analysing both public and private international legal aspects, this cross-disciplinary text promotes an understanding of the ongoing development of child law, children's rights and the protection of the child. Examining the theoretical background to the law, and providing a concise and clear overview of the instruments and institutions that protect children internationally, this text then focuses on key themes and issues in child law and children's rights. This new edition has been updated and revised throughout, including expanded material on the African Charter on Rights and Welfare of the Child as well as discussion of recent landmark developments on the law relating to recruiting child soldiers as a result of Lubanga (2011). The third edition will also include a new case study feature that critically considers key themes and issues in international child law in a real world context. Drawing on a range of legal disciplines, International Child Law is a valuable resource for those in the course of study and research in this area"--